Comparison of Atezolizumab plus Aevacizumab and Atezolizumab plus Aabozantinib for advanced hepatocellular carcinoma: A cost-effectiveness analysis - Heng Xiang; Zhihua She; Liting Wang; Ye Peng; Lei Zhang; Chongqing Tan (PLoS ONE, 2025)
Background Atezolizumab combined with either bevacizumab (atezo-beva) or cabozantinib (atezo-cabo) has been granted approval for the treatment of advanced hepatocellular carcinoma (HCC). Given the current uncertainty among physicians and patients regarding the optimal choice between these two strategies, it becomes imperative to conduct a cost-effectiveness analysis to compare their relative benefits. Objective Assessing the cost-effectiveness of atezo-beva compared to atezo-cabo in the treatment of advanced HCC. Methods Both the network treatment comparison and cost-effectiveness analysis included patients from the IMbrave150 and the COSMIC-312 phase 3 randomized clinical trials. The network treatment comparison which included 761 patients was carried out, and a cost-effectiveness analysis that included 487 patients was conducted by developing a Markov model, both between February and November 2020. The robustness of the model was assessed via one-way and probabilistic sensitivity analyses. life-years, quality-adjusted life-years (QALYs), overall costs, and incremental cost-effectiveness ratios (ICERs) were measured. Results Compared with the atezo-cabo group, atezo-beva group respectively increased 0.528 life years and 0.365 QALYs, with costs per patient increasing by $506,639, and the ICER was $1,388,052.054 per QALY. The one-way sensitivity analysis results indicated that the hazard ratios of OS and HR of PFS were the most sensitive factors in the model. In probabilistic sensitivity analysis, when the WTP threshold is $150,000 per QALY, the cost-effectiveness probabilities of the atezo-beva group and atezo-cabo group were 7.09% and 92.91% respectively. Conclusions Findings from this cost-effectiveness analysis suggested that, compared to atezo-cabo, atezo-beva brought better OS benefits to advanced HCC patients, but also brought higher economic burden, considering the willingness-to-pay threshold was $150 000 per QALY, atezo-beva was not considered cost-effective.